Secondary endolymphatic hydrops: a clinical and literature overview - Aïna Venkatasamy; Aïna Venkatasamy; Aïna Venkatasamy; Aïna Venkatasamy; Anne R. J. Péporté (Frontiers in Neurology)
Introduction and importanceSecondary endolymphatic hydrops (SEH) is a pathologic condition of the inner ear that usually manifests as episodic vertigo and fluctuating hearing loss, overlapping with other temporal bone pathologies and inner ear diseases.MethodsWe searched Pubmed and the Cochrane database for English-language studies published through July 2024.ResultsFifty-four relevant studies and reviews were included in this review on secondary endolymphatic hydrops. This review presents a range of the underlying pathologies in endolymphatic hydrops, along with their corresponding radiological findings, while discussing the associated pathophysiological mechanisms. Secondary endolymphatic hydrops may result from cerebellopontine angle tumors, longstanding inner ear conditions, inner ear malformations, intracranial hypotension and recent investigations have highlighted the role of trauma and inflammation as key factors in SEH development.DiscussionDespite the diverse etiologies of SEH, the findings suggest that many of these conditions share a common final pathway in disrupting endolymphatic fluid balance. This review provides a better understanding of the pathophysiology and etiologies of this intricate disease process, thereby facilitating the diagnosis and treatment of the affected patients.